2012
DOI: 10.1111/jth.12012
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytic variables of thrombin generation: towards a standard procedure and validation of the method

Abstract: Thrombin generation was greatly influenced by preanalytic conditions, demonstrating the need for an international standardized protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
185
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(199 citation statements)
references
References 33 publications
7
185
1
6
Order By: Relevance
“…This may be related to the disparities in preparation modalities (sampling, centrifugation, pooling…), as it is accepted that preanalytical treatment largely influences TGT [16]. Therefore, the main interest of such a material is essentially to act as an "internal quality control" to minimise run-to-run intralaboratory variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the disparities in preparation modalities (sampling, centrifugation, pooling…), as it is accepted that preanalytical treatment largely influences TGT [16]. Therefore, the main interest of such a material is essentially to act as an "internal quality control" to minimise run-to-run intralaboratory variability.…”
Section: Discussionmentioning
confidence: 99%
“…However the method still suffers from an important inter-centre variability and a persistent deficiency in standardisation [14][15][16][17], which makes difficult the design of multicentre studies unless performing TGT in a centralised laboratory. Normalisation of raw results using a normal plasma (pooled or lyophilised) has been proposed for that purpose [14][15][16][17][18]. Recently, a standardized protocol with normalisation of results using a reference plasma (RP) has been shown to reduce lab-to-lab variability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there has been a bifurcation in the commercial TGA into using either chromogenic or fluorogenic assays to determine the levels of thrombin in a sample, whether it be a platelet poor (PPP) or platelet rich (PRP) plasma. PPP is used frequently since it has defined concentrations of tissue factor and phospholipids in each plasma sample, allowing for easy standardization 4. This standardization of thrombograms has resulted in three commercial automated thrombin assays and corresponding software packages: The Behring Coagulation System (BCS), which utilizes chromogenic substrate, and the Technothrombin TGA by Technoclone and Thrombinoscope originally by Thrombinoscope BV and now owned by Diagnostica Stago, Inc. (Asnieres sur Seine, France), which utilize fluorogenic substrates.…”
Section: Thrombin Generation Methodsmentioning
confidence: 99%
“…Recently, Loeffen et al performed a structured evaluation of the effect of preanalytical variables on the results obtained from the CAT ® when thrombin generation was measured in the presence of 0, 1 and 5 pM TF [54]. When comparing three collection devices (intravenous catheters, butterfly needles and straight needle), it was shown that when thrombin generation was measured in the presence of 5 pM TF, no significant difference was found in endogenous thrombin potential (ETP) and peak height between the three collection devices.…”
Section: Preanalytical Variables That Might Affect Thrombin Generatiomentioning
confidence: 99%